Journal of Clinical Immunology International Journal of Inborn Errors of Immunity and Related Diseases - Bonagura, Vincent; Casanova, Jean-Laurent.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Clinical Immunology publishes high impact papers in the area of human immunology that explore the diagnosis, pathogenesis, prognosis, or treatment of human diseases. The Journal is particularly focused on primary immunodeficiencies and related diseases. These include inborn errors of immunity, in the broad sense of the term, their underlying genotypes and their diverse phenotypes, including infection, malignancy, allergy, auto-inflammation, and autoimmunity. We consider a wide range of studies in this area, ranging from genetic discovery, clinical description, immunologic assessment, diagnostic approach, prognosis evaluation, and treatment intervention. Case reports are considered if they are truly original and are accompanied by a succinct review of the relevant medical literature and how the novel case study advances the field. The four categories of papers are detailed in the instructions to authors.
Keywords: Immunology; Diseases; Internal medicine; Medical microbiology; Immunology; Diseases; Internal Medicine; Medical Microbiology